Pengembangan Media Pembelajaran Pencak Silat Berbasis Multimedia Tingkat SMA/MA - Aref Vai; Ramadi Ramadi; Ardiah Juita; Agus Sulastio (Journal Sport Area, 2019)
This research aims to (1) to develop design of learning software as a learning source on the Pencak Silat subject, designing appropriate theory to be used in learning media of Pencak Silat, (2) to determine the feasibility of learning media for Pencak Silat. This research can be categorized as a Research and Development. To get validity product, it would be tested by validity test. Validation was conducted by the expert in Pencak Silat theory, expert in media and trial on a group of students to obtain the advisability of the media that would be used. The validity test used questionnaire test. The data was analyzed by using the quantitative descriptive analysis technique that revealed in scores of distribution and category scales of grading that determined. Based on the evaluation results by the experts of in material aspect owned average score is 4.0 and it has good category. Then the assessment by judges of media aspect obtained average score is 4.34, it has good category. The students’ response in small group average is 4.35 and it has good category. In conclusion, media that developed can be used for learning.